Monogenic Lupus: A Developing Paradigm of Disease - Alperin, Jessie M.; Ortiz-Fernández, Lourdes; Sawalha, Amr H. (Frontiers in Immunology, 2018)
Monogenic lupus is a form of systemic lupus erythematosus (SLE) that occurs in patients with a single gene defect. This rare variant of lupus generally presents with early onset severe disease, especially affecting the kidneys and central nervous system. To date, a significant number of genes have been implicated in monogenic lupus, providing valuable insights into a very complex disease process. Throughout this review, we will summarize the genes reported to be associated with monogenic lupus or lupus-like diseases, and the pathogenic mechanisms affected by the mutations involved upon inducing autoimmunity.